2010
DOI: 10.1183/09031936.00048610
|View full text |Cite
|
Sign up to set email alerts
|

Increased upper airway cytokines and oxidative stress in severe obstructive sleep apnoea

Abstract: Inflammation may contribute to upper airway pathophysiology in obstructive sleep apnoea (OSA). Our objective was to compare upper airway pro-inflammatory cytokine expression, oxidative stress and connective tissue deposition in severe (n525) versus mild (n517) OSA patients.Upper airway surgical specimens were separated by predominance of either mucosal or muscle tissue. Expression levels of interleukin (IL)-1a, IL-6, interferon-c, RANTES (regulated on activation, normal T-cell expressed and secreted), transfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(51 citation statements)
references
References 40 publications
(62 reference statements)
3
47
0
1
Order By: Relevance
“…First, it is associated with an upper airway inflammatory process that has the potential to influence lower airways. In this regard, significant systemic and upper airway inflammation has been reported with OSA [106,107], and Devouassoux et al reported bronchial neutrophilia and a high IL-8 concentration in patients with untreated OSA compared with controls [108].…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%
“…First, it is associated with an upper airway inflammatory process that has the potential to influence lower airways. In this regard, significant systemic and upper airway inflammation has been reported with OSA [106,107], and Devouassoux et al reported bronchial neutrophilia and a high IL-8 concentration in patients with untreated OSA compared with controls [108].…”
Section: Obstructive Sleep Apneamentioning
confidence: 99%
“…Inflammation in the pharyngeal UAW has been linked to profibrotic cytokines and collagen deposition. 45 Collectively, these observations suggest that sustained inflammation leads to UAW remodeling which could adversely affect tissue compliance and/or its mechanical coupling, translating into impaired ability to sustain increased demands. 45 How ICS impact the structure and function of skeletal muscles, such as those of the pharyngeal UAW, remains to be studied.…”
Section: Changes In the Tongue Function In Response To Fp Therapy Andmentioning
confidence: 99%
“…Therefore, inflammation may contribute to upper airway pathophysiology and OSAHS is usually associated with increasing levels of inflammatory cytokines (10)(11)(12). At present, a previous study revealed the correlation between the polymorphism located in the promoter region of the inflammatory cytokine genes and OSAHS (13).…”
Section: Introductionmentioning
confidence: 98%
“…IL-6 is a circulating cytokine, known to be secreted from a number of different cells, including activated macrophages and lymphocytes. Evidence has demonstrated that the plasma levels of pro-inflammatory cytokines, such as IL-6, are observed to be elevated in OSAHS patients, are associated with the severity of disease (12) and are significantly reduced following continuous positive airway pressure therapy (14). It appears reasonable to hypothesize that abnormalities in the IL-6 gene could be relevant to the etiology of OSAHS.…”
Section: Introductionmentioning
confidence: 99%